Hydrodynamics of air and oil–water dispersion/emulsion in horizontal pipe flow with low oil percentage at low fluid velocity. Issue 1 (1st January 2018) - Edwards, Laura; Jebourdsingh, Dillon; Dhanpat, Darryan; Chakrabarti, Dhurjati Prasad
Abstract: The objective of this paper is to investigate the flow regimes of three phase flow, emerged to be as two phase flow. These two phases are air phase and oil dispersed in water phase, in other words the latter phase can be termed as water–oil emulsion phase or simply emulsion phase. Pipeline emulsions flow is inescapable for upstream oil production system in transporting mixtures of crude oil and water. The mixing, turbulence as well as agitation through wellbores, expansion or contraction, valves, pumps, etc. will emulsify either the oil phase or water phase, depending on the volumetric amount of the phases. This is executed in a flow loop system with varying air and liquid-emulsion velocities. The oil percentages to create the water–oil emulsion are varied from 0% to 24%. Flow pattern maps are developed at low range of fluid velocities (0.01–0.1 ms −1 ) and it is compared with established maps. Stratified smooth (SS), stratified to stratified-wavy (SSW), stratified wavy (SW) and stratified wavy with ripples (SWR) are the flow patterns, observed in the experiment. The stratified smooth and stratified to stratified-wavy flow regimes are found to be the most dominant. Oil dispersed in the water (emulsion) phase results a clear distinction of the stratified and the stratified-wavy regimes. An increase in flow regime area occupied by stratified/stratified-wavy in the flow pattern map is evident with increasing oil percent in the dispersed liquid phase. The addition of oil to the liquid phase causes a dampening effect on the flow regime transition, most considerably from stratified to nearly non-stratified flow. This might be attributed to the increase in viscosity at high oil percentages. The pressure drop is not significant in the whole flow phenomena and is found to increase with increasing liquid velocity for all oil percentages as the velocity range of the experiment is very low (0.01–0.1 ms −1 ). Pressure drop and liquid hold up are compared with previous theories and our prediction. Experimental data are predicted with approximately ±10% deviation.